Oxygen uptake response to stroke rate manipulation in freestyle swimming - McLean, S. P.; Palmer, D.; Ice, G.; Truijens, M.; Smith, J. C. (Medicine & Science in Sports & Exercise, 2010)
During gait, humans choose a combination of step length and step rate that minimizes V'O2. However, little work has been reported on the existence of such optimization in swimming.